2013
DOI: 10.5897/jeif12.078
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between energy consumption and national income of Nigeria

Abstract: The purpose of this paper is to examine the causal relationship between energy consumption and National income of Nigeria. The importance of identifying the direction of causality emanates from its relevance in national policy-making issues regarding energy conservation. There are various evidences indicating some level of relation between national income and energy consumption of many countries: developed, developing, and third world alike. A relation that energy consumption enhances national income has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For example, there was only a positive relationship for households using electricity for lighting while it was a negative relationship for households using kerosene. In the same vein, Kabir et al (2013) and Alege et al, (2016) assessed this relationship for Nigeria and found evidence of a strong positive relation that flows from energy consumption to national income. The study by Pachauri et al (2012) also found a bi-directional relationship between energy access and income, implying that increased energy access strengthens growth of income and use of energy tends to rise with income levels.…”
Section: Brief Literature Overviewmentioning
confidence: 95%
“…For example, there was only a positive relationship for households using electricity for lighting while it was a negative relationship for households using kerosene. In the same vein, Kabir et al (2013) and Alege et al, (2016) assessed this relationship for Nigeria and found evidence of a strong positive relation that flows from energy consumption to national income. The study by Pachauri et al (2012) also found a bi-directional relationship between energy access and income, implying that increased energy access strengthens growth of income and use of energy tends to rise with income levels.…”
Section: Brief Literature Overviewmentioning
confidence: 95%